2008
DOI: 10.1088/0957-4484/19/05/055202
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ground hole state of vertically coupled GeSi/Si self-assembled quantum dots

Abstract: We study the ground state of a hole confined in two vertically coupled GeSi/Si quantum dots as a function of the interdot distance and dot composition within the sp(3) tight-binding approach. Both quantum-mechanical tunneling and inhomogeneous strain distribution are included. For pure Ge dots, the strain is found to have two effects on the hole binding energy: (i) reduction of the binding energy below the value of the single dot with increasing dot separation and (ii) molecular bond breaking for intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…BL samples B and D were fabricated by depositing another 2.9 and 3.4 nm Ge on samples of A and C respectively, with a 5 nm Si acting as the spacer layer. In previous studies [13,25], the GeSi QDs separated by a 5 nm Si spacer layer were found to exhibit vertical coupling effects. The topography and current measurements were carried out with a commercial AFM equipment (MultiMode V, Bruker Nano Surfaces Division, Santa Barbara, CA, USA) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…BL samples B and D were fabricated by depositing another 2.9 and 3.4 nm Ge on samples of A and C respectively, with a 5 nm Si acting as the spacer layer. In previous studies [13,25], the GeSi QDs separated by a 5 nm Si spacer layer were found to exhibit vertical coupling effects. The topography and current measurements were carried out with a commercial AFM equipment (MultiMode V, Bruker Nano Surfaces Division, Santa Barbara, CA, USA) at room temperature.…”
Section: Methodsmentioning
confidence: 99%